Synthesis and Characterization of Copoly(Anethole-Stearyl Acrylate) as Phenol Adsorbent - Handayani, Desi Suci; Pramono, Edi; Dewi, Anita Kusuma (Jurnal Kimia Valensi, 2025)
This study aims to synthesize copoly (Anethole-stearyl acrylate, SA) through cationic polymerization at room temperature (28–36°C) under a nitrogen atmosphere. The synthesis was carried out without a solvent using BF3O(C2H5)2 as the initiator. SA was added in varying weights of 2%, 4%, and 6% relative to anethole. The product obtained from the synthesis was then applied as a phenol adsorbent using the batch method at different contact times. FTIR (Fourier Transform Infrared) analysis showed that methoxy group (-OCH3) termination occurred at wavenumber 1147 cm-1, followed by the loss of vinyl group (C=C) at 1633–1654 cm-1. In addition, the loss of =C-H vinyl bending and stretching group absorption occurred at 964–998 cm-1 and 3025–3095 cm-1, respectively. Structural analysis using 1H-NMR showed the loss of the vinyl group proton signal at a chemical shift (δH) of 5.8–39 ppm. The addition of 2%, 4%, and 6% SA led to an increase in intrinsic viscosity of 26.891, 41.093, and 55.336, respectively. The morphology of copoly showed the presence of various cavities. The degradation temperature of the product increased with the addition of SA. During the application of copoly as a phenol adsorbent, the 6% (w/w) concentration had the largest adsorption capacity of 2.22 mg/g.